2008
DOI: 10.1002/cpp.571
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and psychosocial correlates of quality of life in the elderly from a cross‐cultural perspective

Abstract: We compared the quality of life (QOL) of older adults in a post-communist country (the Czech Republic) with those living in traditional western democracies. The sample comprised 1981 respondents aged 60+ (from 60 to 99). The subjective QOL was measured using the WHOQOL-BREF and the add-on module for older adults, the WHOQOL-OLD. The findings showed higher score of depressive symptoms measured by the GDS scale and lower QOL in Czech sample as compared to other centres. Analyses of factors related to QOL of olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
(10 reference statements)
3
26
3
3
Order By: Relevance
“…Social relationships in our study, however were higher than those reported. 22 This study therefore shows, that elderly Thais had a slightly overall lower perception of their quality of life when compared with similar aged population in other countries. The Thai population however had a higher quality of life perception in the domain of social health-social relationshipswhich possibly show, the very close social and family relationship values hold by the Thai culture.…”
Section: Discussionmentioning
confidence: 89%
“…Social relationships in our study, however were higher than those reported. 22 This study therefore shows, that elderly Thais had a slightly overall lower perception of their quality of life when compared with similar aged population in other countries. The Thai population however had a higher quality of life perception in the domain of social health-social relationshipswhich possibly show, the very close social and family relationship values hold by the Thai culture.…”
Section: Discussionmentioning
confidence: 89%
“…A plausible explanation for this observation may be that, compared to older Western adults, older people from post-communist countries generally live in worse socioeconomic conditions, adhere to behavioral norms that are less beneficial for their health, and perceive that they have less control over their health (Bobak et al 2000;Carlson 1998Carlson , 2004Dragomirecka et al 2008;Eikemo et al 2008;Laaksonen et al 2001;Vuorisalmi et al 2008). Bandura (1997) hypothesized that self-efficacy positively affects various aspects of life, including health, by facilitating ''the exercise of control.''…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, older adults from postcommunist countries consistently give lower ratings to their physiological and mental health than do older adults in Western countries (Bobak et al 2000;Carlson 1998Carlson , 2004Dragomirecka et al 2008;Eikemo et al 2008;Laaksonen et al 2001;Vuorisalmi et al 2008). These differences have been explained, for example, by broad socioeconomic factors (Bobak et al 2000;Carlson 1998;Eikemo et al 2008) or behavioral variables, such as exercise or nutritional behavior (Laaksonen et al 2001); however, there is lack of a more detailed analysis of the ways in which behavioral variables (such as PA) and psychological variables (such as self-efficacy) interact in producing various QOL outcomes in older adults from post-communist countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on QOL for persons with dementia have therefore aimed at renewing focus on the qualitative, subjective, psychosocial dimensions of QOL [8][9][10]. Researchers have argued for defining QOL in the context of dementia as the integration of cognitive and physical functioning, activities of daily living, social interaction, and psychological well-being [11].…”
Section: Introductionmentioning
confidence: 99%